Anxiety, movement kinematics, and visual attention in elite-level performers - Causer, J.; Holmes, P. S.; Smith, N. C.; Williams, A. M. (Emotion, 2011)
We tested the predictions of Attentional Control Theory (ACT) by examining the effect of anxiety on attention control and the subsequent influence on both performance effectiveness and performance efficiency within a perceptual-motor context. A sample (N = 16) of elite shotgun shooters was tested under counterbalanced low (practice) and high (competition) anxiety conditions. A head-mounted, corneal reflection system allowed point of gaze to be calculated in relation to the scene, while motion of the gun was evaluated using markers placed on the barrel which were captured by two stationary cameras and analyzed using optical tracking software. The quiet eye (QE) duration and onset were analyzed along with gun barrel displacement and variability; performance outcome scores (successful vs. unsuccessful) were also recorded. QE (Vickers, 1996) is defined as the final fixation or tracking gaze that is located on a specific location/object in the visual display for a minimum of 100 ms. Longer QE durations have been linked to successful performance in previous research involving aiming tasks. Participants demonstrated shorter quiet eye durations, and less efficient gun motion, along with a decreased performance outcome (fewer successful trials) under high compared with low anxiety conditions. The data support the predictions of ACT with anxiety disrupting control processes such that goal-directed attention was compromised, leading to a significant impairment in performance effectiveness.